The Relationship between Farmer Empowerment, Technological Innovation, and Economic Sustainability in the Oil Palm Farming Sector in Kalimantan - Haryono Haryono; Venti Jatsiyah (West Science Agro, 2024)
This study investigates the relationships among Economic Sustainability, Farmer Empowerment, and Technological Innovation and their collective impact on the Farming Sector in the oil palm plantation context of Kalimantan. Using a quantitative approach, data were collected from 230 respondents through structured surveys and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal significant positive relationships between all variables, with Technological Innovation showing the strongest influence on the Farming Sector. Farmer Empowerment also emerged as a critical driver, highlighting the importance of capacity-building and participatory decision-making in enhancing agricultural productivity. Economic Sustainability contributes to sectoral growth by stabilizing income and optimizing resource utilization. These results underscore the importance of integrating empowerment, technological advancements, and economic resilience to foster sustainable development in the farming sector. The study provides actionable insights for policymakers and stakeholders aiming to improve the sustainability and competitiveness of oil palm plantations in Kalimantan.